Effectiveness of Rhodococcus erythropolis strain OPI-01 on the fungal development in winter wheat - ABDULLAH BEHZAD; SIMBO DIAKITE; TAMARA SARZHANOVNA ASTARKHANOVA; ELENA NIKOLAEVNA PAKINA; DUANYO ALLEN; PAI MOHAMMAH MOHAMMADI; OUSMANE DIARRA; FRANCESS SIA SAQUEE (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Behzad A, Diakite S, Astarkhanova TS, Pakina EN, Allen D, Mohammadi PM, Diarra O, Saquee FS. 2024. Effectiveness of Rhodococcus erythropolis strain OPI-01 on the fungal development in winter wheat. Biodiversitas 25: 1063-1070. One of the means of sustainable wheat production is using bacterial pesticides, which can synthesize phytohormonal substances with antibacterial and antifungal action. Therefore, the work aimed to study the effect of different doses of a new growth regulator Restart, ZH (Rhodococcus erythropolis D strain OPI-01) on winter wheat yield. The findings of field experiments on the effect of plant growth regulator R. erythropolis strain OPI-01 method of pre-sowing treatment of seeds (at 0.1 L/t and 0.2 L/t), and soil spraying just before sowing (-0.5 l/ha) revealed that on average, during the 2020-2021 and 2021-2022 seasons, the number of productive stems increased by a margin of 23-30, the number of grains in 1 ear increased in the experimental units by 16.2-19.4%, and the length of the ear by 0.3-0.7cm, gluten varied from 32.3 to 33.8%, yield increased from 27.8-33.0% relative to the control. Disease severity and incidence of powdery mildew, brown rust and Septoria disease in plots amended withR. erythropolis strain OPI-01 was 2-fold less than in the control plots. Research trials show the efficacy of R. erythropolis strain OPI-01 under field conditions as a plant growth regulator and a potential microbial fungicide against some foliar diseases of winter wheat. It would be exciting to study the mechanism of R. erythropolis on wheat pathogens in vitro and in planta which are still less developed in the literature.